Secondary School Renewal: The Effect of Classroom Learning Culture on Educational Outcomes - Cavanagh, Rob (Springer, 2004)
The study was grounded on theoretical propositions and empirical research concerning school effectiveness, classroom effectiveness, school improvement and school renewal. In particular, improving student learning outcomes through improving and renewing schools is dependent on changing classroom cultures of learning and teaching. A model of classroom culture consisting of student educational values (dependent variable), formal learning outcomes (dependent variable), and the attitudes and behaviours of students, teachers and parents (independent variables) was proposed. Hypothesised relationships between the dependent and independent variables were tested by multiple regression analysis of data from 988 students obtained from administration of a Rasch-model instrument assessing classroom culture. The classroom learning attitudes and behaviours of students were found to relate directly to educational outcomes, as were teacher expectations and parent attitudes and behaviours. The attitudes and behaviours of students and teachers towards classroom collaboration and caring were not confirmed to relate directly to learning outcomes. The findings of the investigation are discussed in the light of the theoretical assumptions upon which the study was based, including identification of the implications of the empirical results for understanding and facilitating renewal of secondary schools with the intention of improving educational outcomes in classrooms.